2007
DOI: 10.1016/j.cell.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

RBP2 Belongs to a Family of Demethylases, Specific for Tri-and Dimethylated Lysine 4 on Histone 3

Abstract: Methylation of histones has been regarded as a stable modification defining the epigenetic program of the cell, which regulates chromatin structure and transcription. However, the recent discovery of histone demethylases has challenged the stable nature of histone methylation. Here we demonstrate that the JARID1 proteins RBP2, PLU1, and SMCX are histone demethylases specific for di- and trimethylated histone 3 lysine 4 (H3K4). Consistent with a role for the JARID1 Drosophila homolog Lid in regulating expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
442
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 481 publications
(463 citation statements)
references
References 48 publications
17
442
0
1
Order By: Relevance
“…In this regard, JARID1A, a JmjC domain protein whose mutations are also causally linked with XLMR, and its related proteins have recently been identified as H3K4 demethylases [37,38]. Together these results indicate that appropriate control of histone methylation is critically important for correct cellular identity and differentiation in mammalian development.…”
Section: Discussionmentioning
confidence: 72%
“…In this regard, JARID1A, a JmjC domain protein whose mutations are also causally linked with XLMR, and its related proteins have recently been identified as H3K4 demethylases [37,38]. Together these results indicate that appropriate control of histone methylation is critically important for correct cellular identity and differentiation in mammalian development.…”
Section: Discussionmentioning
confidence: 72%
“…A reasonable explanation for the discrepancy could be that the main part of the detected RBP2-H1-DNA interactions is not directly involved into transcriptional regulation of the corresponding genes, but rather affects other mechanisms of nuclear homeostasis, such as regulation of chromatin structure via histone methylation, as it has been recently suggested for PLU-1/JARID1B and RBP2/JARID1A. 6,7,11,65,66 Posttranslational modification of chromatin by histone methylation has wide-ranging effects on nuclear function, including maintenance of genome integrity, epigenetic inheritance and, of course, transcriptional regulation. 6 Thereby, the regulated genes do not necessarily have to be located in close relationship up-or downstream to the regulatory chromosomal element.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation is added by histone methyltransferases and removed by demethylases. Up to now, more than 20 histone lysine demethylases have been identified that can remove methyl groups from histones in a sequence-and methylation state-specific manner [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The histone lysine demethylases can be divided into two groups with different catalytic mechanisms.…”
Section: Introductionmentioning
confidence: 99%